2009
DOI: 10.1111/j.1365-2125.2009.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy‐led disease and medicine management programme for patients with COPD

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • The concept of self‐management plans for patients with chronic obstructive pulmonary disease (COPD) is derived from their success in asthma management. • It is believed that selected people with COPD may benefit from the early intervention that comes from following self‐management plans, which may prevent a crisis and possibly the need for hospital admission. • There is little published information on clinical pharmacist‐led disease and patient self‐management in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
171
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(186 citation statements)
references
References 43 publications
9
171
1
5
Order By: Relevance
“…In the current study, it was noticed that the total knowledge score of study group was improved than control group post education by two weeks and one month. The result is in line with Khdour et al, (2009) and Jarab et al, (2012) who reported that the study group showed improvement of COPD knowledge when compared with control group [39,40]. Also El-Sayed et al, (2012) found a statistical improvement of total knowledge score among study group than control group post education [41].…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, it was noticed that the total knowledge score of study group was improved than control group post education by two weeks and one month. The result is in line with Khdour et al, (2009) and Jarab et al, (2012) who reported that the study group showed improvement of COPD knowledge when compared with control group [39,40]. Also El-Sayed et al, (2012) found a statistical improvement of total knowledge score among study group than control group post education [41].…”
Section: Discussionsupporting
confidence: 80%
“…Two studies which have incorporated motivational interviewing into self-management interventions have both shown successful improvements in quality of life at 12 months. 10,12 The study by Khdour and colleagues 10 is of particular interest because it also demonstrated reduced health care utilisation, despite the intervention only requiring 1 h of supervision. The incorporation of psychological techniques into self-management programmes is certainly an area for further attention.…”
mentioning
confidence: 99%
“…However, we have seen that some programmes with only minimal supervision have had significant impact on health care utilisation and health status. 10 Another consideration is that some of the extended programmes branded as 'self-management' actually exceed the level of support that many comprehensive pulmonary rehabilitation programmes offer. The COPE studies 7,9 provided individuals with up to twice weekly supervised exercise for up to a year, which surpasses the 6-8 weeks provided by many rehabilitation courses reported in the literature.…”
mentioning
confidence: 99%
“…This may reflect a lower baseline concordance in the ethnic minority target group compared to patients with type 2 diabetes. Concordance is known to be a determinant of adherence, meaning that patient-provider communication has an effect on medication adherence, such that provider communication rated as more collaborative is associated with better medication adherence [31][32][33]. The improvements assessed by patients, pharmacists and social workers show the same tendencies for improvement in knowledge, adherence, confidence in medication taking and the ability to use the medicines correctly.…”
Section: Self-assessed Outcomesmentioning
confidence: 99%